Phytochemistry and Chemdraw : Innovative Learning Materials for Implementing the "Merdeka Belajar" Program: Fitokimia dan Chemdraw : Bahan Pembelajaran Inovatif untuk Melaksanakan Program “Merdeka Belajar - Kristanti, Alfinda Novi; Aminah, Nanik Siti; Ramadhan, Rico; Haq, Kautsar Ul; Wardana, Andika Pramudya; Suhaili, Suhaili; Hariyanto, Geraldo Figo (ANDAN JEJAMA: Indonesian Journal of Community Engagement (IJCE), 2023)
The city of Mataram, the capital of West Nusa Tenggara province, consists of 6 sub-districts and 50 sub-districts and has 28 public and private high schools. Lecturers and students of the Department of Chemistry, who are members of the community service team, on August 5th, 2023 carried out a workshop for chemistry and biology teachers in the City of Mataram. The title of the activity was "Application of Phytochemical Screening as a medium to increase the insight of Biology and Chemistry High School Teachers in Mataran City, NTB as an alternative implementation of Merdeka Belajar". The workshop was held at SMAN 5 Mataram City involving 51 chemistry and biology teachers as participants. The material provided includes Phytochemicals and the Chemdraw application. Both of these topics are given by lecturing and discussion and also complemented by practical activities. The successful of the activity is reflected in the increase in posttest scores compared to the pretest score. Evaluation of activities in the form of filling out the questionnaires by participants also reflected the participant satisfaction, in which the majority of participants gave positive answers to each question. Similar activities remain relevant and still need to be carried out, especially in areas outside Java to broaden teachers' insight